Applying Hands-on Inquiry Learning in Physical Chemistry Teaching Practice to Improve Teaching Quality - Deng, Xiaojun; Zhao, Jingfeng; Tian, Qinqin; Wang, Haibo (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Physical chemistry is an important theoretical basic course that supports the development of medicine and pharmacies. Physical chemistry teaching is usually a process of traditional teaching and passive acceptance. The teaching method is singular, and students lack an interest and the ability of autonomous learning. Objectives: The purpose of the study is to explore the application of a hands-on inquiry learning strategy blending independent learning based on information resources flipped classroom teaching, the student-centered micro class auxiliary teaching mode in physical chemistry courses to improve student learning outcomes and develop active learning ability. Materials and Methods: Eighteen students in the experimental pharmacy major class, grade 2020, were recruited to study in a physical chemistry course that applies hands-on inquiry learning. Formative and summative evaluation were used to evaluate the students' achievements related to active learning goals. After the study was completed, a survey was administered to demongstrate the teaching results. Results: Student hands-on inquiry learning performance was positively correlated with the final scores. The results show that comprehensive scores of students of 2020 grade (experimental group) are significantly better than grade 2019 students (control group); in particular, the theoretical scores of 2020 grade students are better, and the data are significantly different. The questionnaire showed that most students believed that hands-on inquiry learning strategy blending independent learning improved their high-level cognitive skills and enhances their social cohesion and sense of responsibility. Conclusion: The hands-on inquiry teaching strategy developed in this study effectively improved students' performance in formative and summative assessment, and provided a reference basis and informative entry point for the implementation of active learning strategy in higher pharmaceutical education.
Keywords: Hands-on inquiry learning; Higher pharmacy education; Active learning; Teaching strategy; Problem-based learning